Penerapan Algoritma Fp-Growth Dalam Menemukan Hubungan Data Prestasi Akademik Dengan Etika Mahasiswa (Study Kasus : POLTEKKES KEMENKES RI Medan) - Pelawi, Bobby Pranata (STMIK Budi Darma, 2019)
The development of data storage technology is growing rapidly, the more evolving times, the more a person's ability to collect and process data is growing. Data collected with large sizes can be used for analysis, the results of which are valuable information for the future. One of the institutions that can not be separated from data accumulation is universities. RI Ministry of Health Poltekkes Medan is a higher education program that has midwifery and nursing studies. With so many students, academic achievement and student ethics must be in line so that the achievements and ethics of students can be in line with both. Because there are so many data of students who have different academic achievements and ethics, research needs to explore data held by the Indonesian Ministry of Health Polytechnic in Medan. The data used is the final GPA of students and student ethical values from final year students. This research is considered very necessary so that the relationship between student achievement and ethics can be in line. A classification technique is needed which is one of the techniques of data mining to analyze the data from the Indonesian Ministry of Health Polytechnic in Medan. By applying this technique a FP-growth algorithm will be built where the data we input is made into an FP-tree and gets the emergence value so that the data entered can be interconnected.